Menelisik Pesan atau Amanat dari Komik Webtoon Canvas 7 Years Relationship Karya Franncellyn Alexandria - Muhammad Rifki Rahardian Putra; Muhamad Burhanudin (Institut Agama Islam Negeri Curup, 2022)
This study focused on analyzing one of the intrinsic elements in comics, namely the mandate (moral message) offered by the author of the 7 Years Relationship comic published in digital comic media, Webtoon Canvas. The stories developed have a mandate, namely the importance of helping others, repaying the kindness of others who have helped us, and so on. Also in this comic, the author tucked away about the dangers of a child being restrained by his parents to choose his